Delirium management in 2024: a status check and evolution in clinical practice since 2016 - Coolens, Oliver; Kaltwasser, Arnold; Melms, Tobias; Monke, Stefanie; Nydahl, Peter; Pelz, Sabrina; Haken, Rebecca von; Hasemann, Wolfgang (Intensive & critical care nursing, 2025)
Background - Delirium in patients on intensive care units (ICU) can lead to prolonged length of stay, cognitive decline and higher mortality. Implementing delirium management is a challenge for healthcare workers. Between 2016 and 2024, several quality improvement projects were performed in German speaking countries. These projects included founding a delirium society, distributing delirium related curricula, awards, surveys, webinars, public materials, and others. The aim was to assess the current state of delirium management in 2024 and identify changes in prevention, detection, and treatment since 2016. - Method - Repetition and comparison of a survey for delirium management from 2016 in 2024. Questions included items for hospital and ICU characteristics, present delirium structures, processes, assessment routines, barriers, and others. The survey was distributed in a snowball system in German speaking countries. Data were analysed statistically. - Results - Participating ICU in both surveys (2016: n = 559, 2024: n = 447) had similar basic characteristics and enabled comparison. Use of validated delirium assessment tools slightly increased from 56.8 % (n = 398) in 2016 to 74.4 % (n = 438) in 2024. Significant improvement rates were identified from 2016 to 2024 in use of validated assessments (56.8 % vs. 72.8 %), prevention programs (34.6 % vs. 44.7 %), information materials for patients and families (18.9 % vs. 33.8 %), and others. Conversely, there was decreased implementation in dementia screening (23.7 vs. 14.8), use of restraints (68.3 % vs. 58.4 %), and others. The top barrier, lack of time and staff, remained in first place. - Conclusions - The comparison of two large surveys in 2016 and 2024 indicate a slightly cultural shift in delirium management in German speaking countries. Open quality improvement projects might increase delirium awareness and contribute to an ongoing cultural change. - Implications for practice - Improvement projects addressing barriers and delirium-specific awareness are essential to improve and sustain delirium management practices in ICU settings.